Awareness of the psychological bias of naïve realism as a subtle strategy for improving stereotypes towards Moroccan women in Spain. (May 2022) - Cuadrado, Isabel; López-Rodríguez, Lucía; Brambilla, Marco
Abstract: The present research explored whether the exposure to the psychological bias of naïve realism (i.e., the conviction that one's own views are objective, and the other's views are biased) could promote stereotype change along the dimensions of morality, sociability, and competence. Due to their double discrimination, we considered Moroccan women living in Spain as the target group. Participants (307 Spaniards; M age = 35.92, SD = 13.37; 61.6% women) were randomly assigned to a naïve realism (vs. control) condition and were further asked to evaluate Moroccan or Spanish women. Findings reveal that Moroccan women were evaluated as more moral, sociable and competent in the naïve realism than in the control condition. The ingroup favouritism towards Spanish women (compared to Moroccan women) disappeared in the moral dimension: once aware of the naïve realism bias, participants perceived Moroccan women as honest, sincere and trustworthy as Spanish women. Taken together, our findings suggest that making people aware of the bias of naïve realism might be beneficial for intercultural relations as it contributes to enhance outgroup evaluations and reduce the ingroup bias on morality, a core dimension in social perception. Highlights: The exposure to the psychological bias of naïve realism promotes stereotype change. Moroccan women are evaluated as more moral, sociable and competent in the naïve realism than in the control condition. Once aware of the naïve realism bias, participants perceived Moroccan women as moral as Spanish women.